Setting vehicle side impact safety design targets using a regression-based approach. (26th February 2007) - Cheruvu, Kalyan S.; Deb, Anindya; Neal, Mark O.; Wang, J.T.
This paper presents a methodology for setting design variable targets for vehicle side impact safety using a statistical data-based approach. It is assumed that vehicles are to be designed for a high star rating in the Lateral Impact New Car Assessment Programme (LINCAP) conducted by the National Highway Traffic Safety Administration (NHTSA). Accordingly, the Thoracic Trauma Index (TTI) is the relevant injury parameter, which is expressed as a function of design variables in the form of a multilinear regression relation. The expression for TTI (front), which has been derived in an earlier work, has been complemented here with a new regression-based relationship for TTI (rear) through extensive statistical analysis of publicdomain LINCAP test data posted by NHTSA. Using 'best subset' regression analysis, significant variables affecting TTI (rear) have been identified and the latter has been expressed as a function of these variables yielding a high degree of correlation with test data. Using a simple computer-based tool, it is shown how numerical targets for design variables can be arrived at within predefined ranges for a given value of TTI (front or rear).